Customer Experience and Physical Environment Increasing Customer Satisfaction through Customer Value - Fadillah, Muhammad Abi (ESENSI: Jurnal Manajemen Bisnis, 2024)
Positioning is a matter in any business including the service industry. In general, any restaurant provides all convenience facility for customer. This study aims to increase customer satisfaction with specific unique positioning mediating by customer value in pet-friendly policy at Kina Café & Bar. The population of this study consists of visitors to Kina Café & Bar. Accidental sampling technique was used to select 250 respondents. Data analysis was conducted using Structural Equation Modeling (SEM) with the assistance of SmartPLS software. The results of this study indicate that customer experience has a significant impact on customer value and satisfaction. Additionally, customer experience has a significant impact on customer satisfaction through customer value. The physical environment significantly affects customer value and satisfaction. Additionally, customer value has a significant impact on customer satisfaction. Therefore, the physical environment indirectly affects customer satisfaction through customer value.